The Effect of Financial Literacy and Digital Literacy on Employee Performance at PT XYZ, Tangerang City - Hanggono Arie Prabowo (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines how financial literacy and digital literacy affect employee performance at PT XYZ in Kota Tangerang, addressing gaps on combined literacy impacts and managerial mediation. Using a quantitative explanatory design, financial literacy (X1) and digital literacy (X2) were tested as predictors of employee performance (Y) via multiple linear regression in SPSS 22. A purposive sample of 48 employees provided data collected March–June 2023. Assumption tests supported parametric analysis. The model explained 67.1% of performance variance (R2 = 0.671), with both literacies showing positive relationships with employee performance. Findings imply that integrated capacity-building in financial and digital skills—paired with managerial development and digital adoption strategies—can substantially improve individual and organizational outcomes in Tangerang’s competitive MSME context.